DESAIN PENGUKURAN KINERJA KOPERASI SIMPAN PINJAM (KSP) CU ABC DI KABANJAHE DENGAN MENGGUNAKAN METODE ANALISIS REARLS - Situmorang, Aston L.; Sagala, Habinsaran Maruli Tua (UNIKA Santo Thomas, 2024)
Savings and loan cooperatives must be able to create trust from both the community and members. To gain this trust, savings and loan cooperatives must have a good level of health. One of the cooperative financial performance appraisal systems is the PEARLS analysis system. The purpose of this study was to design a tool used to determine the health level of the Savings and Loans Cooperative (KSP) CU ABC di Kabanjahe-Kabanjahe in 2021 using the PEARLS analysis system. This research is a quantitative descriptive study using primary data and secondary data obtained from the Savings and Loans Cooperative (KSP) CU ABC di Kabanjahe-Kabanjahe. The data analysis technique used to answer these problems is PEARLS analysis. The results of this study indicate that the protection aspect shows less than ideal conditions, both from the availability of risk reserve funds for total bad loans of more than 12 months (P1) and the availability of risk reserve funds and allowance for bad loans of 1-12 months (P2). The protection aspect in the ratio P3, P4, P5 also shows that there is no default on loan repayments in the cooperative for more than 12 months. The P6 ratio shows results that are not ideal. Most aspects of an effective financial structure show that it is not ideal, especially for the ratios of E5, E7, E8, and E9. This aspect also shows that at ratio E1 the percentage of outstanding loans is ideal. In the ratio E2, E3, E4 indicates that the investment has been going well. Ratio E6 explains that the cooperative does not have loans to other parties. The aspect of asset quality, especially the ratio of total non-performing loans to total receivables, shows a ratio that is not ideal, while the ratio of non-productive assets to total assets shows an ideal ratio. Aspects of rates of return and cost, for two indicators, namely the ratio of member stock deposits and the ratio of operating costs, indicate ideal conditions. Aspects of liquidity, the ratio of liquidity to non-shares, the conditions are not ideal. Aspects of signs of growth that have indicators of member growth ratios that are not ideal and the ratio of growth of total assets to total assets at the beginning of the year indicate ideal conditions. The ratio of S1, S2, S4, S6 and S7 shows that there is no ideal growth. The S3, S5, S8 and S9 ratios are showing signs of ideal growth.